Analysis of social–Psychological factors and financial incentives in demand response and residential energy behavior - Chen, Chien-fei; Xu, Xiaojing; Cao, Zhuolin; Mockus, Audris; Shi, Qingxin (Frontiers in Energy Research, 2023)
Demand response (DR) programs are promising approaches to balance supply and demand, as well as reduce or shift peak hour loads, but the impact of residents’ behavioral patterns and social-psychological factors on these programs are not well understood. We use an extended model of the Theory of Planned Behavior to understand how these factors, demographics, and household characteristics influence U.S. residents’ DR behaviors (i.e., adjusting A/C, shifting washer and dryer time of use). Data were collected from 826 residents in the U.S. and found that both thermal comfort needs and participants’ age increase their financial incentives requested to accept higher A/C temperatures while someone is home. Thermal comfort needs are also associated with increased financial incentives requested for higher A/C temperature when no one is home. Elderly residents tend to request higher financial incentives for shifting washer and dryer usage than younger residents. Our regression model of residents’ intention to engage in electricity curtailment behaviors showed attitudes toward energy saving to be the strongest predictor, followed by perceived behavioral control, subjective norms, cost concern, environmental concern, and energy-saving habits; suggesting the potential of social-psychological variables in shaping energy consumption behaviors. This study provides insights needed for designing effective DR programs and analyzing residential energy behavioral patterns in a broad context.